2010
DOI: 10.1002/ijc.25105
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of tumorigenesis and metastasis of hepatocellular carcinoma by shRNA interference targeting on homeoprotein Six1

Abstract: We previously demonstrated that the overexpression of homeoprotein Six1 in hepatocellular carcinoma (HCC) patients is associated with venous infiltration, advanced pathologic tumor metastasis (pTNM) stage and poor overall survival rate (Ng et al. Br J Cancer 2006;95:1050-5). In this study, short hairpin RNA (shRNA) interference approach was used to suppress the expression of Six1 in a metastatic HCC cell line MHCC97L. Stable transfectant MHCC97L-shSix1 carrying Six1-specific shRNA plasmid was established to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 32 publications
2
52
0
Order By: Relevance
“…MTT (Invitrogen) assay and colony formation assay were performed as previously described (18). Cells were treated with drugs for 72 hours and 2 weeks for MTT assay and colony formation assay, respectively.…”
Section: Proliferation Assaysmentioning
confidence: 99%
See 3 more Smart Citations
“…MTT (Invitrogen) assay and colony formation assay were performed as previously described (18). Cells were treated with drugs for 72 hours and 2 weeks for MTT assay and colony formation assay, respectively.…”
Section: Proliferation Assaysmentioning
confidence: 99%
“…cDNA microarray analysis cDNA microarray profiles of MHCC97L, MHCC97L/ CisR, and MHCC97L/DoxR were conducted by gene chip system Human U133 Plus 2.0 (Affymetrix Inc.), by Genome Research Centre, The University of Hong Kong (18). Microarray data (GEO accession number: GSE54175) were analyzed by GeneSpring Version 10 (Agilent Technologies).…”
Section: Proliferation Assaysmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, SIX1 overexpression correlates with poor prognosis in numerous tumor types, including breast cancer (10), suggesting that it plays an important role not only in tumorigenesis, but also in metastasis. Indeed, SIX1 is critical for metastasis in different models of cancer, including rhabdomyosarcoma (11), hepatocellular carcinoma (12), and breast cancer (10). Using an experimental metastasis model, we recently demonstrated that SIX1 plays a role in the later stages of metastasis through its ability to upregulate TGF-β signaling (10).…”
Section: Introductionmentioning
confidence: 99%